CORONAVIRUS DISEASE-19: A HOLISTIC PERSPECTIVE - RAJ, POOJA; BHATI, KIRTI; PATWARDHAN, RAVINDRA (Innovare Journal of Ayurvedic Sciences, 2021)
Even when the predictions of effective specific antiretroviral treatment improved after 1996, many scientists and health professionals stayed committed to a dominant role of prevention over treatment and care. With the growing need for vaccines and safer drugs, greater attention is now toward the traditional system of medicine. Charak Samhita explains epidemics and its etiological factor in Janapadodhwamsa Adhyay of Vimansthan 3. Ayurveda and Yoga have immersed to have great combat with coronavirus disease (COVID-19) to maintain your overall health. The present study is aimed to get, a holistic approach that suggests a preventive approach and strengthening of Bala and Oja. Ayurveda and Yoga give importance to physical immunity and also psychological immunity as well. By following Rasayan, Sadvritta, Acharasayan, Astanga Yoga and Satvik Karma one manages a proper balance and Tridosha along with physical and mental health. There is a need to explore the holistic care modules stated in different Ayurvedic classical texts and Yoga for COVID-19.